Cardiovascular Disease Risk Profiling among First-Degree Relatives of Premature Coronary Artery Disease Patients - Shah, Nischal; Gajurel, Ratna Mani; Poudel, Chandra Mani; Ghimire, Roshan; Yadav, Sutap (Nepalese Heart Journal, 2023)
Background and Aims: First-degree relatives of patients with premature coronary artery disease are at heightened risk of cardiovascular events due to the synergy of genetic and environmental factors. The aim of this study was to assess the cardiovascular disease (CVD) risk factors and to estimate cardiovascular risk in first-degree relatives of patients with premature CAD. Methods: The study was conducted among first-degree relatives of patients with coronary artery disease in a tertiary care hospital in Kathmandu. A total of 144 first-degree relatives aged 18 years or older participated in this study. Age and gender matched subjects with no clinical evidence of CAD and no history of premature CAD in frst degree relatives were recruited as controls. The cardiovascular risk of study participants was assessed using the American Heart Association (AHA) Cardiovascular Risk Assessment Tool. Result: The study age group was between 18 to 59 years. The mean age of the subjects was 35.54 ± 10.57 years and 63.19% of subjects were men. A statistically significant number of first-degree relatives of premature CAD were found to be hypertensive and had metabolic syndrome. CVD risk factors like physical inactivity, smoking, diabetes, and dyslipidemia were found in 46.5%, 47.22%, 13.2%, and 52.01%, of the study participants, respectively. Conclusion: The study highlights the widespread presence of risk factors and underlying medical conditions among young study participants both with and without a family history of premature CAD. Appropriate direction based on opportunistic screening programs and risk stratifcation should be initiated which can play an important role in the primary prevention of early CAD.